Use the product rule to simplify the following expression. Assume that variables represent nonnegative real

numbers.
square root x^13

square root x^13 blank (Please type an exact answer using radicals as needed.)

1 answer

To simplify the expression \(\sqrt{x^{13}}\), we can use the property of square roots that states \(\sqrt{a^b} = a^{b/2}\).

Using this property, we have:

\[ \sqrt{x^{13}} = x^{13/2} \]

Next, we can express \(x^{13/2}\) in terms of radicals. The exponent \(13/2\) can be split into an integer part and a fractional part:

\[ \frac{13}{2} = 6 + \frac{1}{2} \]

Thus, we can express this as:

\[ x^{13/2} = x^6 \cdot x^{1/2} = x^6 \cdot \sqrt{x} \]

Combining this, we can write the entire simplification as:

\[ \sqrt{x^{13}} = x^6 \sqrt{x} \]

So the final answer is:

\[ x^6 \sqrt{x} \]